“PENGARUH KINERJA AKUNTANSI DAN LEVERAGE TERHADAP HARGA SAHAM” (Studi Empiris pada Perusahaan Bank, Property dan Real Estate yang terdaftar di Bursa Efek Indonesia Periode 2011-2013) - Muhammad Habibie Al Hamzah (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2014)
The purpose of this research was to determine the influence of accounting earning, Return On Assets, Return On Equity, and leverage on stock prices. Methods of sampling using purposive sampling. This research was conducted on 54 companies in sector banks, property and real estate listed in Indonesia Stock Exchange 2011-2013 period. Model analysis of the data in this research using multiple regression analysis. The results showed that accounting earnings, Return On Assets and leverage have an influence on stock prices. While the Return On Equity has not been shown to have an influence on stock prices. In this research the most influential dominant variable to stock prices is accounting earnings. Keywords : Accounting earnings, ROA, ROE, leverage and stock price.